Sistem Sosial Ekonomi Dalam Lingkungan Kerja Es Teh Indonesia Cabang Jalan Jawa, Jember - Fiki Febriananda; Hafizh Ahmad F. R. H; Ahmad Dzikri Aljasiri (Institut Nalanda, 2023)
This research is based on the level of public interest in a relatively new franchise in the beverage sector, namely Indonesian Es Tea. Departing from the level of enthusiasm of the customers becomes a benchmark for looking for unique phenomena in this franchise, namely about wages and the welfare of its workers. This study aims to reveal the systematics of franchising with various kinds of class structure arrangements in it using ethnographic methods. Several things were obtained in the form of transparency of regulations in the store and distribution of wages in it. In this study, the consequence is that the confidentiality of informants and data must really be considered.